Transcriptome Profiles Reveal a 12-Signature Metabolic Prediction Model and a Novel Role of Myo-Inositol Oxygenase in the Progression of Prostate Cancer - Liu, Wangrui; Xiang, Jianfeng; Wu, Xinrui; Wei, Shiyin; Huang, Haineng; Xiao, Yu; Zhai, Bo; Wang, Tao (Frontiers in Oncology, 2022)
Prostate adenocarcinoma (PRAD) is an extremely common type in the urinary system. We sought to establish a metabolic signature to identify novel targets in a predictive model of PRAD patients. A total of 133 metabolically differential expressed genes (MDEGs) were identified with significant prognostic value. LASSO regression analysis constructed a 12-mRNA signature model, a metabolic prediction model (MPM), in 491 PRAD patients. The risk score of the MPM significantly predicted the progression of PRAD patients (p<0.001, AUC=0.745). Furthermore, Myo-Inositol Oxygenase (MIOX), the most pronimently up-regulated metabolic enzyme and hub gene in the proteien-protein interaction network of the MPM, showed significant prognostic implications. Next, the expression of MIOX in normal prostate tissue was detected to be lower than in PRAD tissue, and high MIOX expression was significantly associated with progressive progression (p=0.005, HR=2.274) in 81 PRAD patients undergoing first-line androgen receptor signaling inhibitor from the Renji cohort. Meanwhile, MIOX was significantly involved in the abnormal immune infiltration of the microenvironment and associated with DNA damage repair process of PRAD. In conclusion, this study provides the first opportunity to comprehensively elucidate the landscape of prognostic MDEGs, establish novel prognostic modeling of MPM using large-scale PRAD transcriptome data, and identify MIOX as a potential prognostic target in PRAD patients from multiple cohorts. These findings help manage risk assessment and provide valuable insights into treatment strategies for PRAD.